Pengelolaan Zakat Di Indonesia - Nasution, Adanan Murrah (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
Zakat is the primary means of communication between man and another man in bermasyarat sake compose a harmonious and humane life . The role of Zakat , both property and tithes would be more visible subtle and implemented together with other instrumental value that is usury. Obligation of alms giving firm and absolute top of every Muslim, premises object property that is property and income that have fulfilled the obligation of zakat and charity penunian -value embodied wisdom and universal values that benefit the community life and poverty pengentas.Keywords : Zakah, management, poverty